Magnesium-waste for as a green hydro-reactive material in hydrogen production: Modification, hydrolysis, cost and environmental impact assessment - Yilmam, Merve; Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In this study, waste magnesium (Mg) chips as a green hydro-reactive material in hydrogen production evaluated by modification, hydrolysis, cost, and environmental impact assessment. Mg chips modified via ball milling or mixing with additives such as sodium formate (SF), formic acid (FA), and acetic acid (AA) and tested through controlled hydrolysis experiments. Mg-based hydro-reactive materials coded as M-9 modified by ball-milling with FA and mixing with AA showed improved hydrogen production rate up to 4000 mL H2 min-1 g-1 and yield of 900 mL H2 g-1. Furthermore, a detailed environmental impact and cost assessment performed to evaluate the feasibility of proposed system as green and economically viable route for hydrogen production. The green modification procedure of M-9 had 12.32 MJ kg-1, 1.66 kg CO2 kg-1, 59.29 kg CO2eq kg-1 of environmental impact assessment of process values and greenness index of 0.73.
Keywords: Magnesium waste; Hydro-reactive; Formate; Modification; Hydrogen; Greenness; EMBODIED ENERGY; THERMAL-DECOMPOSITION; GENERATION; PERFORMANCE; CHLORIDE; COMPOSITE; MECHANISM; ALLOYS; IRON; Chemistry; Electrochemistry; Energy & Fuels